A chef's guide to gelling, thickening, and emulsifying agents [ (CRC Press, 2015)
The use of food texturizing agents, such as gels, thickeners, and emulsifiers, has been steadily increasing in the culinary industry. Understanding how to use these texturizing agents is important for chefs of all levels, from professionals to culinary students and amateur cooks. This new work from Ali´cia Foundation, the culinary research center driven by famed chef Ferran Adria`, provides a clear and practical guide for any chef who wants to work with these texturing agents.Collaboration between scientists, technicians, and chefs has resulted in unique and creative culinary uses for many commo.